Prevalence of parenting styles during the early childhood years: Does parents’ socioeconomic status matter? - Gyeltshen, Lotey (JECCE, 2023)
The paper was aimed at exploring the prevalence of parenting styles during the early childhood years in Bhutan. The population of the study were parents (N = 433) who were selected through a purposive sampling technique. A survey questionnaire and semi-structured questions were used to collect data. Descriptive analysis and one-way ANOVA were used as statistical techniques. The findings of the study showed that an authoritative parenting style was more prevalent during the early childhood years. However, some features of authoritarian and permissive parenting styles are present. Further, parenting styles also differed by parents’ socio-economic status. It was found that an authoritative parenting style differed by the parents’ education qualifications but did not differ by the parents’ income and marital status. In addition, the authoritarian parenting style differed by the parents’ educational qualifications and income level, while it did not differ by the parents’ marital status. However, parents’ parenting styles did not differ by their educational qualifications, income level, or marital status.